Short-term effects of the “I Spy Feelings” program on emotion regulation in 5- to 6-year-old children - Arthur, Annaliese; McDevitt, Maryanne; Rooney, Rosanna M.; MacLeod, Amber; Kane, Robert T.; Tonta, Kate; McMillan, Kaitlin; Peckover, Jacob; Baughman, Natalie (Frontiers in Psychology, 2023)
Mental health difficulties in early childhood can have a debilitating and ongoing impact throughout an individual’s life; emotion regulation can serve as a protective factor. Therefore, evidence-based prevention programs that teach children effective skills and strategies for emotion regulation are needed. As part of the Aussie Optimism pilot study evaluating the “I Spy Feelings” program, this study aims to assess the short-term effects of the program after on emotion regulation in pre-primary aged children after two months via a longitudinal cluster randomised controlled trial. Participants included parents (N = 73) of 5- to 6-year-old children attending four different Catholic primary schools. Children from two of the schools were allocated to the intervention group where they participated in the program (N = 33), while children from the other two schools were allocated to the control group where they did not (N = 40). At each time point, all parents completed abridged Children’s Emotional Management Scales measuring how well parents believe their child is able to cope with anger, sadness and worry. A significant intervention effect was found for the outcome of anger coping such that parents whose children were in the intervention group reported significantly greater improvement in their children’s ability to cope with anger compared to parents whose children were in the control group. No significant effect was found for the outcome of sadness, and results for the worry subscale were inconclusive due to unacceptable internal consistency. The present study provides insight into the benefit of programs designed to enhance the emotion regulation skills of very young children. Further follow-up is needed to assess whether the “I Spy Feelings” program has lasting effects.